The influence of information literacy skills on students’ choice of competition type: A study of library visiting day competition - Indah Wijaya Antasari (Social Sciences and Humanities Open)
On September 14, 1995, President Soeharto inaugurated the observance of Library Visiting Day in Indonesia. Accordingly, in 2022, the UIN Saizu library observed this annual event by organizing various competitions such as book review, creative video presentations, reading ambassadors, and library representatives with the International Federation of Library Associations and Institutions (IFLA) information literacy standards. In this regard, this study is aimed at analyzing the impact of library visiting day competitions on students’ information literacy skills. A quantitative research method was employed using Structural Equation Modelling (SEM) with the SmartPLS4 application. The study population comprised 158 students who participated in the library visiting day competition at UIN Saizu library, of which 38 respondents were selected. Furthermore, the analysis was conducted by calculating second orders with an embedded two-stage approach. The first stage was concentrated on measuring the dimensions of the information literacy variable, but in the second, variables were calculated based on their dimensions. The results showed that neither the faculty nor the study level of students significantly affected their literacy ability or choice of competition. However, it was found that students' literacy skills significantly influenced their choice of competition types. This result implies that students with higher literacy levels tend to select competitions with higher levels of difficulty.